Relationship Between Compliance with Oral Hypoglycemic Drugs and Hs-CRP Levels in Type 2 Diabetes Mellitus - Intan Nur Ramadhani; Sakti, Hari Saktiningsih (Jurnal Biologi Tropis, 2025)
Type 2 diabetes mellitus is a chronic condition with hyperglycemia due to insulin resistance and impaired insulin secretion, where oral medication non-compliance can worse glycemic control and trigger inflammation characterized by elevated hs-CRP levels. This research aims to examine the relationship between compliance with oral hypoglycemic drugs and hs-CRP levels in patients with diabetes mellitus. This study used a cross-sectional design with purposive sampling of 20 patients with type 2 diabetes mellitus at Puskesmas Mojolaban. Compliance was assessed by MARS-10 and hs-CRP levels were measured by immunoturbidimetry, then analyzed by descriptive statistics and correlation with Fisher’s Exact Test. The results showed that 95% of respondents who adhered to their medication had normal hs-CRP levels (<0.85 mg/L), while 5% of non-adherent respondents had abnormal hs-CRP levels (>0,85 mg/L). The Fisher’s Exact Test result in a p-value = 0.050, indicating a significant relationship between compliance with oral hypoglycemic drugs and hs-CRP levels. Compliance to oral medication in patients with type 2 diabetes mellitus may be an effective strategy to suppress systemic inflammation (hs-CRP) and prevent macrovascular compliactions.